Requirements of the supply chain due diligence act of Germany on labour, and responsibilities of Vietnamese enterprises in the supply chain - Hoi, Dao Xuan (Edelweiss Applied Science and Technology, 2025)
This paper analyzes the supply chain due diligence (SCDD) requirements outlined in Germany’s SCDD Act (LKSG), with a focus on labor protection and the responsibilities of Vietnamese enterprises in the context of global economic integration. The findings indicate that while compliance with international SCDD standards offers significant benefits—such as enhancing corporate reputation and expanding market opportunities—Vietnamese enterprises also face challenges related to infrastructure, resources, and adaptation to new regulatory demands. This paper proposes strategies to improve internal supply chain governance and recommends proactive governmental support to facilitate the adoption of international standards. These insights contribute to a deeper understanding of the German law’s impact on supply chain management and provide strategic directions for Vietnamese enterprises to enhance corporate social responsibility in the global market.